1972
DOI: 10.1073/pnas.69.5.1322
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Yolk DNA from Xenopus laevis Oocytes Ovulated In Vitro

Abstract: High molecular weight DNA was isolated from the yolk platelets of Xenopus laevis oocytes ovulated in vitro. Yolk DNA has the same buoyant density in CsCl gradients as mitochondrial and nuclear DNAs, and, like them, it is double-stranded. Yolk DNA behaves like nuclear DNA, and not like mitochondrial DNA, upon renaturation after denaturation. The molecules are always linear. Cytochemical and biochemical controls preclude the possibility that the yolk DNA might be contaminated by nuclear or mitochondrial DNA. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1977
1977
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…(2) The processes involved may include the degradation and further utilization of the yolk DNA. Similar to earlier work in other systems (Hanocq et al, 1972), we have found a significant amount of DNA associated with the highly purified yolk fraction from dormant cysts (Marco et al, 1983); the fate and molecular characteristics of this DNA are being studied now in our laboratory. This second type of role is more likely associated with the type A-I/A-I* yolk granule associated enzyme.…”
Section: Discussionsupporting
confidence: 85%
“…(2) The processes involved may include the degradation and further utilization of the yolk DNA. Similar to earlier work in other systems (Hanocq et al, 1972), we have found a significant amount of DNA associated with the highly purified yolk fraction from dormant cysts (Marco et al, 1983); the fate and molecular characteristics of this DNA are being studied now in our laboratory. This second type of role is more likely associated with the type A-I/A-I* yolk granule associated enzyme.…”
Section: Discussionsupporting
confidence: 85%
“…A similar but more thorough paper found high molecular weight DNA isolated from the yolk platelets of Xenopus oocytes. The yolk DNA has the same buoyant density in CsCl gradients as mitochondrial and nuclear DNAs, and, like them, it is double-stranded (Hanocq et al, 1972). The authors conclude that the yolk DNA is an endogenous component of the yolk platelets.…”
Section: Nucleic Acidsmentioning
confidence: 86%
“…Analyses of the DNA content of amphibian eggs by classical methods show that they contain a large excess of DNA over the expected 4C value ; part of this excess DNA is in the mitochondria, but studies on homogenates from oocytes show that more than 65% of cytoplasmic DNA is recovered in the yolk platelets. Studies on yolk DNA (Hanocq et al, 1972) have shown that it is made of linear double-stranded molécules somewhat smaller than those obtained by similar methods from Xenopus chromatin (respective mol.wts. 26x 10* and 40x 10*).…”
Section: Oogenesismentioning
confidence: 85%